Metabolite T 2 relaxation times decrease across the adult lifespan in a large multi‐site cohort - Hupfeld, Kathleen E.; Murali‐Manohar, Saipavitra; Zöllner, Helge J.; Song, Yulu; Davies‐Jenkins, Christopher W.; Gudmundson, Aaron T.; Simicic, Dunja; Lamesgin Simegn, Gizeaddis; Carter, Emily E.; Hui, Steve C. N.; Yedavalli, Vivek; Oeltzschner, Georg; et al. (Magnetic resonance in medicine, 2025)
Relaxation correction is crucial for accurately estimating metabolite concentrations measured using in vivo MRS. However, the majority of MRS quantification routines assume that relaxation values remain constant across the lifespan, despite prior evidence of T changes with aging for multiple of the major metabolites. Here, we comprehensively investigate correlations between T and age in a large, multi-site cohort. We recruited approximately 10 male and 10 female participants from each decade of life: 18-29, 30-39, 40-49, 50-59, and 60+ y old (n = 101 total). We collected PRESS data at eight TEs (30, 50, 74, 101, 135, 179, 241, and 350 ms) from voxels placed in white-matter-rich centrum semiovale (CSO) and gray-matter-rich posterior cingulate cortex (PCC). We quantified metabolite amplitudes using Osprey and fit exponential decay curves to estimate T . Older age was correlated with shorter T for tNAA , tCr , tCr , tCho, and tissue water (CSO and PCC), as well as mI and Glx (PCC only); r = -0.22 to -0.63, all p < 0.05, false discovery rate (FDR)-corrected. These associations largely remained statistically significant when controlling for cortical atrophy. By region, T values were longer in the CSO for tNAA , tCr , Glx, and tissue water and longer in the PCC for tCho and mI. T did not differ by region for tCr . These findings underscore the importance of considering metabolite T differences with aging in MRS quantification. We suggest that future 3T work utilize the equations presented here to estimate age-specific T values instead of relying on uniform default values.